Patients’ Satisfaction about Quality and Services of Food in a Tertiary Military Hospital (Journal of Armed Forces Medical College, Bangladesh, 2022)
Introduction: Patients’ satisfaction has become a key criterion by which quality of health care services is evaluated. Quality of food and its services in a hospital is an important component of treatment process since it sometimes is a part of treatment and often affects the patients' satisfaction.Objectives: To determine the level of patients’ satisfaction about quality of food and services and to identify the factors affecting it.Materials and Methods: This cross-sectional observational study was carried out from July 2018 to June 2019 in a tertiary military hospital, Dhaka. Structured questionnaires were used as data collection instruments and were analyzed by SPSS version 23.Results: Out of 184 respondents’ majority (60.3%) were satisfied with hospital food and food services. About 94%, 91.3%, 88%, 84.8%, 3.2% and 77.2% respondents were satisfied with amount, warmth, cleanliness of utensils, cleanliness of food servers, attitude and behaviour of food servers and food distribution time respectively. Relationship between overall satisfaction level and different aspects related to hospital food and food services was detected by chi-square and Fisher’s exact test. In logistic regression analysis result showed that taste of food, food distribution time, cleanliness of food servers and cleanliness of ward/cabin were statistically significant and most important determinants of patients’ satisfaction with the food served in hospital.Conclusion: Improving taste of food, ensuring cleanliness of the food servers and ward and adjusting food distribution time are required to improve the level of overall patients’ satisfaction towards hospital food and food services.JAFMC Bangladesh. Vol 17, No 1 (June) 2021: 3-6